A Study on the Influence Factors of Agricultural Carbon Emissions in Hunan Province Based on Random Forest Model - Liu Yaxiang; Liang Tao; Cheng Jing (E3S Web of Conferences, 2024)
Agricultural carbon reduction contributes to the realization of “carbon peak and carbon neutrality” strategy. This article analyzes the previous years’ data of agricultural carbon emissions in Hunan Province, and obtains the variation of carbon emissions; Using the random forest method to analyze the influence factors of agricultural carbon emissions in Hunan Province, it is proven that unit crop production value, unit energy carbon emissions in agriculture, and unit agricultural GDP energy consumption are the three most critical factors affecting agricultural carbon emissions in Hunan Province. LDMI method is used for validation. Sensitivity analysis was conducted on factors such as agricultural energy consumption, total production value of AFAF(Agriculture, forestry, animal husbandry, and fishing), total agricultural production value, crop yield, crop planting area, and non-urban population. The first five changes have a positive impact on agricultural carbon emissions, while non-urban population has a downward and then upward trend.